CD40 levels in plasma are associated with cardiovascular disease and in carotid plaques with a vulnerable plaque phenotype and remodelling. (25th November 2020) - Shami, A; Edsfeldt, A; Shore, A.C; Natali, A; Khan, F; Nilsson, J; Lutgens, E; Goncalves, I
Abstract: Background and purpose: CD40 and CD40 ligand (CD40L) are costimulatory molecules and members of the TNF receptor superfamily well known for their involvement in inflammatory and autoimmune diseases. This study uses two large human cohorts – the SUrrogate markers for Micro- and Macro-vascular hard endpoints for Innovative diabetes Tools (SUMMIT) and the Carotid Plaque Imaging Project (CPIP) – to explore the potential of plasma or intra-plaque expression of CD40 and CD40L as biomarkers and to locally affect plaque stability. Methods: Proximity Extension Assay (PEA) technique was used to measure soluble CD40 and CD40L (sCD40 and sCD40L) in plasma from 1437 subjects from the SUMMIT cohort, the majority of which (80%) with pre-existing cardiovascular disease, and in atherosclerotic plaque homogenates from 199 subjects of the CPIP cohort undergoing carotid endarterectomy. The Mann-Whitney U test was used to compare groups and Spearman's rank correlation/the Chi-square test was used to assess correlations. Multiple comparisons were corrected for using the Holm-Šídák test. A logistic regression model was used to test for associations with future cardiovascular events and mortality. Results: In the SUMMIT cohort both plasma CD40 and CD40L levels were elevated in individuals with a history of stroke (p=0.000030 and p=0.020, respectively), while sCD40 levels also were higher in individuals with a prior acute myocardial infarction (p=0.016). Plasma levels of sCD40 correlated with carotid plaque burden (as measured by ultrasound imaging, r=0.355, p<1x10–16) and were associated with future cardiovascular events over a three year-follow up period (p=0.02, hazard ratio 1.3, 95% C.I: 1.042–1.625). sCD40 and sCD40L were associated with a plaque phenotype characterized by the strong presence of features both of vulnerability such as high content oxidized low-density lipoprotein (LDL; r=0.236, p=0.004 and r=0.259, p=0.0037, respectively) and pro-inflammatory cytokines (e.g. tumour necrosis factor-α: p=3.1x10–7 and p=0.0006, respectively) and low calcium content (r=−0.208, p=0.012 and r=0.268, p=0.00034, respectively). Conclusion: High plasma CD40 and CD40L levels are associated with symptomatic cardiovascular disease. Plasma CD40 levels correlate with the severity of carotid atherosclerosis and are associated with an increased risk for future cardiovascular events. Additionally, intra-plaque levels are associated with a vulnerable plaque phenotype. Our findings thus support the value of sCD40 and sCD40L both as biomarkers and therapeutic targets for cardiovascular disease. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The Swedish Heart and Lung Foundation (1) and the Swedish Research Council (2)